The Impact Of Reading Habits On Cognitive Learning Outcomes In Indonesian Language Of 4th Grade Students Of Sdn Kebun 1 - Nihayatul Wafiroh; Tyasmiarni Citrawati (STKIP Rokania Pasir Pangaraian, 2023)
This research comes from the problem that students' reading habits are lacking such as when there are empty hours or during breaks do not take the time to read, rarely visit the library and reading corner. Based on these problems, researchers are interested in knowing whether habits have an impact on the learning outcomes of Indonesian language students in grade 4 SDN Kebun 1. The method used in this research is a qualitative method with a descriptive model and data collection with documentation, questionnaires, and observation. Data on learning outcomes were taken with documentation from students' daily tests. Other data was taken from a questionnaire distributed to 4th grade students of SDN Kebun 1, totaling 19 students on March 11, 2023. Observation was used to see how often grade 4 students visit the library and reading corner. Based on the results of the research that has been carried out, it is found that reading habits have an impact on the cognitive learning outcomes of 4th grade students of SDN Kebun 1. This can be proven from the students' reading time, the longer the time spent reading the higher the learning outcomes obtained so that parents and teachers can instill reading habits in children from the earliest possible age. However, not only reading habits can lead to learning outcomes, there are still many other things that have an impact on student learning outcomes.